Interpreters’ choice of style in interpreted lawyer-client interviews: An ethnographic approach - Xu, Han (Meta, 2024)
While professional interpreters are trained to interpret in direct speech style, using the “direct interpreting approach” (Hale 2007), studies show that some interpreters deviate from this style, with implications for their role performance. Few of these studies, however, have examined the interpreters’ style choice in relation to their professional qualifications and ethics. Drawing on data from an ethnographic investigation of interpreted lawyer-client interviews in Australia, this study explores interpreters’ choice of interpreting style in line with their professional qualifications, the reasons behind their choice and the implications for their role performance. It found that trained interpreters used direct speech consistently and understood the rationale behind this ethical requirement. Untrained interpreters either ignored this norm or had difficulty adhering to direct speech style and its associated interpreting approach in a consistent manner. They shifted to reported speech on various occasions to achieve different communication purposes, some of which indicate their assumption of roles not stipulated in their professional ethics. The untrained interpreters’ lack of compliance with the normative practice relates to their inadequate understanding of some aspects of the interpreter’s ethical role.